Glass ceiling in the Nigerian banking sector: Evidence from senior male and female employees - Dennis G. Pepple; Raphael Oriaghe Oseghale; Elly Nmecha; Joyce Nwagu (Contemporary Economics, 2024)
This work is licensed under a Creative Commons Attribution 4.0 International License. The banking and finance sector is a major employer in many countries, especially in emerging economies. Decisions made in the sector have significant implication on the economy. There is evidence that decision- making has significant implications for organisations (and, by extension, the economy) when their manage- ment teams are diverse in terms of gender. Yet only a few women are promoted to executive and managerial roles. This research qualitatively explores how senior male and female employees experience the glass ceiling in the Nigerian banking sector. We conducted 40 interviews, comprising 20 senior male executives and 20 senior female executives from 4 banks in Nigeria. Our study reveals that the glass ceiling is characterised by a male-dominated meritocratic organisational culture that is driven by the goal of profit maximisation, consis- tent with the meritocratic perspective of role congruity theory. We contribute to the extant literature on this topic by examining how women's strategies for navigating this landscape (namely, the self-directed actions women take in order to progress in their careers) diminish men's view of the glass ceiling, suggesting a para- dox of meritocracy. This study contributes significantly to the debates on the future of women's progression in the banking sector in an emerging economy.
Keywords: J7; 330; glass ceiling; organisational culture; paradox of meritocracy; societal culture; Nigerian banking sector